Investigate of unsimilar effect of longer rest interval in multiple sets by performing deload repetition training regimes to micro strength gain change on light weeks of weightlifters - Kahraman, Y.; Varol, I.; Sahan, A.; Hocalar, A. (Scientific Journal of Sport and Performance, 2024)
Continuum zone repetition training strategies are one of repetition manipulation both multiple set and repetition zone periodization on weightlifters. The present study was aimed to strength level on weightlift exercise condition of weightlifting athletes, deload repetition resistance training regimes involved in proper rest interval and repetition range by performing multiple set and longer rest interval within different maximize performance on light weeks. The experimental study was conducted to 2 olympic, 1 national, 6 professional weightlifters participated on age (16-21 years) this study. With study maximize performance condition over 3 week resistance training finished to weightlifters. Priority experimental pre-test and post-test outcomes after resistance training showed significant different (p < .05) in dynamic strength to countermovement jump shrug (p = .035; d = 0.69; = 17.78%). However, significant different in low load repetition failure to overhead press (p = .007; d = 0.86; = 5.56%), high load repetition failure to bent-over row (p = .017; d = 1.14; = 8.00%), low and high load repetition failure to countermovement jump shrug (p = .017; d = 1.17; = 13.78% - p = .048; d = 0.73; = 5.44%), in localize endurance not significant performance level to resistance exercise performance. However, isometric strength detected to overhead press (p = .016; d = 1.30; = -0.72%), bent-over row (p = .012; d = 1.67; = -0.51%) and countermovement jump shrug (p = .004; d = 2.45; = -0.48%) in weightlifters. Unsimilar longer rest interval multiple set configuration suggested to maximize strength gain on short time deload repetition training regimes by manipulated repetition and set addition rest interval currently manipulation of weightlifters.